1994
DOI: 10.1113/jphysiol.1994.sp020469
|View full text |Cite
|
Sign up to set email alerts
|

Transient and long‐lasting actions of 5‐HT on rat dentate gyrus neurones in vitro.

Abstract: 1. The actions of 5-hydroxytryptamine (5-HT) on rat dentate gyrus neurones were measured with conventional intracellular recording techniques in brain slices maintained in vitro at 32 'C. 2. Bath application of 5-HT (03-100 uM) hyperpolarized the membrane potential and reduced the input resistance; these effects persisted in tetrodotoxin (1 UM) and were abolished by MDL 73,005EF, a 5-HTlA receptor antagonist. 3. Local application of 5-HT via a pressure pipette also elicited a hyperpolarization and a reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 39 publications
7
53
1
Order By: Relevance
“…The extrasynaptically located inhibitory serotonin 1A receptor on pyramidal cell dendrites (19) can be activated by serotonin released not only through spillover from synaptic terminals but also from nonsynaptic varicosities, resulting in further reduction of the temporal and spatial precision of the serotonergic control. Activation of the excitatory G protein-coupled serotonin 2A receptors expressed by GABA-expressing (GABAergic) interneurons (20) was also shown to have a long-lasting effect on pyramidal neurons (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…The extrasynaptically located inhibitory serotonin 1A receptor on pyramidal cell dendrites (19) can be activated by serotonin released not only through spillover from synaptic terminals but also from nonsynaptic varicosities, resulting in further reduction of the temporal and spatial precision of the serotonergic control. Activation of the excitatory G protein-coupled serotonin 2A receptors expressed by GABA-expressing (GABAergic) interneurons (20) was also shown to have a long-lasting effect on pyramidal neurons (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well demonstrated that the glutamatergic transmission inhibits cell proliferation in the DG via NMDA receptors (Cameron et al, 1995;Gould et al, 1997;Nacher et al, 2001), which are expressed by granule cells, as 5-HT1A receptors. Hyperpolarization of these cells following activation of postsynaptic 5-HT1A receptors (Piguet and Galvan, 1994) would counterbalance this negative control. Finally, long-term analyses of neurogenesis following acute or chronic activation of 5-HT1A receptors indicate that the increases in cell proliferation are not transient and are followed by a significant augmentation in the number of newly formed neurons in DG.…”
Section: Regulation Of Cell Proliferation and Neurogenesis In The Dgmentioning
confidence: 99%
“…Similarly to the hippocampus, modulation of GABA release from interneurons (mainly inhibition by 5-HT 1A receptors and stimulation by 5-HT 2 and/or 5-HT 3 receptors) has also been observed in other areas, among which dentate gyrus [132,152], enthorinal cortex [40,165], piriform cortex [115], frontal and anterior cingulate cortex [192].…”
Section: Modes Of Interactionmentioning
confidence: 99%